Analisis perbandingan peramalan permintaan pasir silika dan batu tras menggunakan metode single exponential smoothing dan moving average - Pramillia, Nazhiifah Ananda; Syaifullah, Hafid (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
XYZ Company is a subsidiary of PT. Z which is one of the largest companies in Indonesia. XYZ Company has various businesses in the sales and distribution sector, one of which is raw materials for making cement. The purpose of this study is to find out and analyze the demand for silica sand and tras stone. in December 2024. This study uses the Single Exponential Smoothing and Moving Average method with the help of Microsoft Excel in forecasting the demand for silica sand and tras stone in XYZ company for raw materials for cement making using historical data on the demand for silica sand and tras. The results of the correct forecast to forecast the demand for silica sand and tras stone for December 2024, the most accurate results were obtained using the Single Exponential Smoothing method of 5,064.05 and 4,063.45 with MAD values; MSE; and MAPE of 1,677.69 and 2,285.85; 4,997,901.53 and 7,442,297.34; and 46% and 62%.